Antecedentes del Sistema de Educación Mitad Trabajo Mitad Estudio en China: Evidencias de la combinación del trabajo productivo con la enseñanza (1912-1958). - Arana, David Ibarra (Humania del Sur: Revista de Estudios Latinoamericanos, Africanos y Asiáticos)
This paper describes some educational experiences and ideas suggested by Dewey, Tao, The Work Study Movement and Mao in China between the beginning of the twentieth Century and 1919 as evidence of the implementation of productive work in formal education. Based on the analysis of the active role of ideas in institutional conformation, an ideological divergence between these experiences and ideas, and the "Half Work, Half Study" Educational System (HWHSES) implemented in 1958 in China.